Cannabidiol or ketamine for preventing the impact of adolescent early drug initiation on voluntary ethanol consumption in adulthood - Colom-Rocha, Carles; Bis-Humbert, Cristian; García-Fuster, M. Julia (Frontiers in Pharmacology, 2024)
Background Few studies have previously evaluated the long-term impact of initiating the combined use of alcohol and cocaine early-in-life during adolescence. Our preclinical study characterized changes in affective-like behavior and/or voluntary ethanol consumption emerging later on in adulthood induced by a prior adolescent drug exposure, as well as tested therapeutical interventions (i.e., cannabidiol or ketamine) to prevent the observed effects.We performed 3 independent studies with male and female Sprague-Dawley rats, treated in adolescence (postnatal days, PND 29-38) with non-contingent paradigms of ethanol, cocaine, their combination or vehicle. Later on, adult rats were (1) scored for their affectivelike state (forced-swim, elevated-plus maze, novelty-suppressed feeding, sucrose preference),(2) allowed to freely drink ethanol for 6 weeks (two-bottle choice), or (3) treated with cannabidiol or ketamine before given access to ethanol in adulthood. Results No signs of increased negative affect were observed in adulthood following the adolescent treatments. However, adolescent ethanol exposure was a risk-factor for later developing an increased voluntary ethanol consumption in adulthood, both for male and female rats. This risk was similar when ethanol was combined with adolescent cocaine exposure, since cocaine alone showed no effects on later ethanol intake. Finally, rats exposed to adolescent ethanol and pretreated in adulthood with cannabidiol (and/or ketamine, but just for females) reduced their ethanol voluntary consumption. Conclusions Our data provided two therapeutical options capable of preventing the impact of an early drug initiation during adolescence by decreasing voluntary ethanol consumption in adult rats.• Adolescent ethanol exposure is a risk-factor for later voluntary ethanol consumption.• This increased vulnerability is observed both for male and female rats.• Adding cocaine exposure in adolescence does not increase the observed risk.• Cannabidiol (and/or ketamine, but just for females) reduced the observed risk.